2000
DOI: 10.1523/jneurosci.20-22-08620.2000
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Arousal Regions Are Activated during Modafinil-Induced Wakefulness

Abstract: Modafinil is an increasingly popular wake-promoting drug used for the treatment of narcolepsy, but its precise mechanism of action is unknown. To determine potential pathways via which modafinil acts, we administered a range of doses of modafinil to rats, recorded sleep/wake activity, and studied the pattern of neuronal activation using Fos immunohistochemistry. To contrast modafinil-induced wakefulness with spontaneous wakefulness, we administered modafinil at midnight, during the normal waking period of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
288
3
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(309 citation statements)
references
References 40 publications
13
288
3
5
Order By: Relevance
“…Modafinil is thought to primarily act on hypocretin (orexin)-containing neurons in the hypothalamus and on the tuberomammillary nucleus, both of which are implicated in the regulation of wakefulness. 16 In contrast, in autopsy studies of polio patients, many other regions in the brainstem and basal ganglia were also affected. 2,3 Also, histologic, imaging and neuroendocrine studies in polio patients showed that the motor cortex, basal ganglia, and reticular activation system bore the brunt of injury.…”
Section: Discussionmentioning
confidence: 95%
“…Modafinil is thought to primarily act on hypocretin (orexin)-containing neurons in the hypothalamus and on the tuberomammillary nucleus, both of which are implicated in the regulation of wakefulness. 16 In contrast, in autopsy studies of polio patients, many other regions in the brainstem and basal ganglia were also affected. 2,3 Also, histologic, imaging and neuroendocrine studies in polio patients showed that the motor cortex, basal ganglia, and reticular activation system bore the brunt of injury.…”
Section: Discussionmentioning
confidence: 95%
“…Thus the absence of sleep rebound associated with modafinil could also be interpreted as absence of catecholamine exhaustion as the waking effect of modafinil does not seem to depend on endogenous catecholamines [35]. Moreover, no signs of direct neuronal depolarization/excitation on target cells have been reported for modafinil, even though diffuse expression of immediate early gene c-fos [41], or enhanced histamine release [42] occurred with high doses of modafinil. These effects can be attributed to a direct consequence of the sustained waking induced by modafinil rather than a direct pharmacological targeted action per se.…”
Section: Absence Of Sleep Reboundmentioning
confidence: 97%
“…The compound does not activate and may inhibit phosphatidylinositol hydrolysis in mouse cortical brain slices yet it does stimulate a prazosin-or terazosinblockable phosphorylation of MAP kinase (MAPK) both in vitro and in vivo but only at fairly high concentrations (10 À4 M) (Stone et al, 2001d). Since it was the only (presumed) a 1 -agonist used in the above study, the possibility that stress may have acted on other neuronal systems necessary for modafinil action such as DA, orexin, or GABA (Ferraro et al, 1997;Scammell et al, 2000) cannot yet be excluded.…”
Section: Effects Of Stress and Depression On Epi-a 1 -Systemmentioning
confidence: 99%